Sistem Pengelolaan Arsip Dinamis Aktif di Kantor Perpustakaan, Arsip, dan Dokumentasi Kabupaten Pesisir Selatan - Fajri, Hamdani; Syahyuman, Syahyuman (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
This paper discusses about system of the process of active dynamic archives at library, Archives and Documentation office of Pesisir Selatan Region. The purposes of the research are to find:(1) The system of the process of active dynamic archives such as: The saving instrumentation, the saving system, the lending, the inventing, keeping, moving and destroying archives system. (2)Â The problems which face at the library, archives and documentation of Pesisir Selatan. The data were becolletted by doing interview, library research and observation. Based on the research, it can be concluded that its processing was not maximum. Keywords: archive management, dynamic archive